A framework for work-life balance practices: Addressing the needs of the tourism industry - Deery, Margaret; Jago, L. (Henry Stewart Publications, 2009)
This paper examines the key issues associated with work-life balance (WLB) with a particular focus on practices within the tourism industry. It provides an overview of the general literature and then the research that relates specifically to WLB in the tourism industry. It builds on previous research in this area to present an adapted framework for addressing the key variables of WLB that can be tested in subsequent research.